STEM-based E-learning: Implementation and Effect on Communication and Collaboration Skills on Wave Topic - Wiyono, Ketang; Sury, Kristylia; Hidayah, Riski Nur; Nazhifah, Nauratun; Ismet, Ismet; Sudirman, Sudirman (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
Communication and collaboration are essential skills that students must master in the 21st century. These skills can be raised and improved through systematic learning, such as the STEM approach. This study aims to determine the effect of STEM-based e-learning applications on high school students’ 2C (communication and collaboration) skills on wave material. This type of research was quasi-experimental, using the pretest-posttest method. The population of this study was 11th-grade students of the science program at public senior high school number 2 Palembang. Data analysis techniques used quantitative data analysis techniques to analyze the data collected from students’ 2C skills achievement scores. The results of data analysis on the average pretest on communication skills got a value of 54, while collaboration skill was 55. After applying STEM-based e-learning on wave material, the average post-test scores on communication and collaboration skills were 82.7 and 85.7. It showed that the students’ 2C skills increased after using STEM-based e-learning on wave material. The main finding of this study was that the application of STEM-based e-learning on wave material effectively improved students’ 2C (communication and collaboration) skills. It was evidenced by the analysis results of the N-gain test, which showed that students with communication skills scored 0.62 in the medium category and 0.68 in the medium category for collaboration skills.